Risk of Acute Kidney Injury after Off-Pump Coronary Artery Bypass Grafting in Patients with Poor Glycemic Control - Aqeel Ahmad; Yasir Khan; Waseem Rehman; Naeem Ullah; Fauzia Zafar; Muhammad Rassan (Proceedings)
Introduction: Coronary artery bypass grafting (CABG) is a commonly performed procedure in ischemic heart disease (IHD) patients. Acute kidney injury (AKI) is a frequent complication of CABG. Many patients undergoing surgery have Diabetes Mellitus, which increases risk of AKI after CABG. Limited work has been done to see the impact of poor glycemic control on incidence of AKI after off-pump CABG. However, local data on the subject was missing especially using OFF PUMP technique.